Complex Interplay of Eastern Bloc SMEs Trade Credit Determinants: Changes due to the Global Financial Crisis - Tamara Teplova; Tatiana Sokolova; Kristina Galenskaya; Mariya Gubareva (Complexity)
We investigate whether the determinants of small and medium enterprises’ (SMEs) trade credits taken for purchasing fixed assets suffered substantial changes due to the global financial crisis (GFC). The geographical focus of this paper covers 18 former Eastern bloc countries. The data sample comprises opinions of the SMEs top managers relative to the trade credit financing. The two-step Heckman procedure is applied to study complexity of the trade credit determinants. We find that before the GFC the equity concentration and inflation have negatively impacted the trade credit while foreign ownership and company’s longevity have had a positive effect. The GFC has changed this complex relationship. We evidence that, after the GFC, equity concentration and state subsidies have a positive effect.